Nitrogen losses from the human small bowel: obligatory losses and the effect of physical form of food. Issue 6 (June 1988) - Chacko, A; Cummings, J H
Abstract : The amount and form of nitrogen lost from the human small intestine and the dietary factors which influence it have been studied in six ileostomists. Over a six day period the subjects were fed a series of diets including low nitrogen (LND) 0.17 g N/day, LND + soya beans (5.87 g N/day) and a high fibre diet (HFD) (10.6 g N/day). The soya beans were fed either whole or pureed to test the effect of physical form of food. Total N, protein, amino acids, urea, and ammonia were measured in ileostomy effluent which was collected throughout the study. Total N excretion was LND 0.91 (0.04) (SE) g/day; LND + whole soya beans (WSB) 2.26 (0.15) g/day; LND + pureed soya beans (PSB) 1.42 (0.12) g/day (WSB v PSB, p less than 0.001); and HFD 2.17 (0.11) g/day (HFD v PSB, p less than 0.001, HFD v WSB, NS). N losses as urea, ammonia, and free amino acids were less than 10-15% of total N, the remainder being protein (48-51%) and (by difference) peptides (20-30%). Eighty to 85% of effluent N was in the insoluble (pellet) fraction except on the low N diet where it was 66%. The physical form of food clearly influenced N digestibility in the soya beans whilst changes in dietary fibre seem not to have a significant effect.